Enhancing resolution of free-flow zone electrophoresis via a simple sheath-flow sample injection - Yang, Ying; Kong, Fan-Zhi; Liu, Ji; Li, Jun-Min; Liu, Xiao-Ping; Li, Guo-Qing; Wang, Ju-Fang; Xiao, Hua; Fan, Liu-Yin; Cao, Cheng-Xi; Li, Shan (Electrophoresis, 2016)
In this work, a simple and novel sheath‐flow sample injection method (SFSIM) is introduced to reduce the band broadening of free‐flow zone electrophoresis separation in newly developed self‐balance free‐flow electrophoresis instrument. A needle injector was placed in the center of the separation inlet, into which the BGE and sample solution were pumped simultaneously. BGE formed sheath flow outside the sample stream, resulting in less band broadening related to hydrodynamics and electrodynamics. Hemoglobin and C‐phycocyanin were successfully separated by the proposed method in contrast to the poor separation of free‐flow electrophoresis with the traditional injection method without sheath flow. About 3.75 times resolution enhancement could be achieved by sheath‐flow sample injection method.